Novel Adsorbents for Canola Oil Physical Refining: Mesoporous Calcium and Magnesium Silica Aerogel - Soylu, Tulay Merve; Karakuzu-Ikizler, Burcu; Terzioglu, Pinar; Yucel, Sevil (WILEY-V C H VERLAG GMBH, 2025)
The refining process of edible oil is essential for extending its shelf life by removing contaminants that negatively affect quality and consumer acceptance. This study evaluates the effectiveness of calcium silica aerogel, magnesium silica aerogel, a combination of both, bentonite, Trisyl, and various aerogel combinations in a single-stage physical refining process of crude canola oil. Calcium and magnesium silica aerogels were synthesized via the precipitation method from water glass and subsequently dried under ambient pressure using an air dryer. The synthesized aerogels were characterized using scanning electron microscopy, Fourier-transform infrared spectroscopy, N2 adsorption-desorption analysis and bulk density measurements. The surface areas of the calcium and magnesium aerogels were found to be 45.67 m2/g and 616.46 m2/g, with densities of 0.15 g/cm3 and 0.18 g/cm3, respectively. The adsorption capacities of these adsorbents for free fatty acids, peroxides, and color pigments in crude canola oil were examined. The aerogels reduced free fatty acid levels by 14% to 47%, and their use in the refining process produced oil with a lighter color. Notably, the most effective peroxide removal, reaching 53.4%, was achieved with a 50:50 combination of aerogels. These findings demonstrate the potential of calcium and magnesium silica aerogels as effective adsorbents for removing impurities from edible oils.
Keywords: Calcium silica aerogel; Canola oil; Magnesium silica aerogel; Refining; FATTY-ACIDS; SUNFLOWER; OXIDE; CONSTITUENTS; REMOVAL; WASTE; Chemistry